2021
DOI: 10.1155/2021/3928323
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia May Synergize with Hypomethylation in Establishing Trained Immunity and Promoting Inflammation in NASH and NAFLD

Abstract: We performed a panoramic analysis on both human nonalcoholic steatohepatitis (NASH) microarray data and microarray/RNA-seq data from various mouse models of nonalcoholic fatty liver disease NASH/NAFLD with total 4249 genes examined and made the following findings: (i) human NASH and NAFLD mouse models upregulate both cytokines and chemokines; (ii) pathway analysis indicated that human NASH can be classified into metabolic and immune NASH; methionine- and choline-deficient (MCD)+high-fat diet (HFD), glycine N-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 117 publications
2
24
0
Order By: Relevance
“…However, immunological characters of endothelial cells have been poorly characterized due to the fact that endothelial cells have not been recognized as innate immune cells in the field. To fill in this significant knowledge gap, ten years ago based on more than ten major innate immune functional aspects that are shared by the prototypic innate immune cell type -macrophages and endothelial cells, we proposed a new concept that endothelial cells are innate immune cells (2,4), which was further supported by our experimental data (5)(6)(7)(8)(9)(10)(11)(12)(13) analyses (Shao et al,15). The Molecular Innate Immunity field is continuously evolving, and we greatly appreciate the Molecular Innate Immunity section editors gave us this opportunity to organize this Research Topic and work with other investigators to explore this important topic further.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, immunological characters of endothelial cells have been poorly characterized due to the fact that endothelial cells have not been recognized as innate immune cells in the field. To fill in this significant knowledge gap, ten years ago based on more than ten major innate immune functional aspects that are shared by the prototypic innate immune cell type -macrophages and endothelial cells, we proposed a new concept that endothelial cells are innate immune cells (2,4), which was further supported by our experimental data (5)(6)(7)(8)(9)(10)(11)(12)(13) analyses (Shao et al,15). The Molecular Innate Immunity field is continuously evolving, and we greatly appreciate the Molecular Innate Immunity section editors gave us this opportunity to organize this Research Topic and work with other investigators to explore this important topic further.…”
Section: Introductionmentioning
confidence: 66%
“…Trained immunity is a novel mechanism for persistent hyperactivation and synergies between DAMPs/PAMPs One of the significant progresses in the innate immunity field is the identification of innate immune memory or trained immunity (15)(16)(17)(18). Ever since investigators found memory adaptive immune cells such as memory T cells and memory B cells, we have always been puzzled by two questions whether innate immune cells have memory functional status for challenged stimuli and whether innate immune cells have memory cell subtypes similar to that of adaptive immune cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is known as trained immunity or innate immune memory [ 59 , 80 ]. Trained immunity can occur in several traditional innate immune cells such as monocytes/macrophages, natural killer (NK) cells, dendritic cells (DCs), aortic cells, innate immune functions of T cells, and Treg cells, as well as in non-traditional immune cells such as vascular smooth muscle cells (VSMCs), endothelial cells (ECs), hepatocytes, and fibroblasts [ 59 , 81 , 82 , 83 , 84 , 85 ]. Trained immunity can be induced by several pathogen-associated molecular patterns (PAMPs)/danger-associated molecular patterns (DAMPs) stimuli such as lipopolysaccharides (LPS), β-glucan, Bacillus Calmette–Guerin (BCG), oxidized low-density lipoprotein (ox-LDL), and high-fat diet [ 86 , 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…TI is important for host defense, vaccine response, and promoting the pathogenesis of chronic inflammations including metabolic CVDs such as atherosclerosis. In contrast to the memory function in the adaptive immune system with special cell subsets to carry out memory function such as memory T cells and memory B cells ( 22 ), TI can occur in innate immune cells such as monocytes/macrophages ( 23 ), natural killer cells, endothelial cells (ECs) ( 6 , 11 , 24 ), vascular smooth muscle cells ( 25 , 26 ), and nonimmune cells, such as fibroblasts ( 7 ) and hepatocytes ( 27 , 28 ). Of note, we recently reported that CD4 + Foxp3 + regulatory T cells (Tregs) have many active innate immunity pathways ( 29 , 30 ), and can sustain their immunosuppressive functions ( 31 ) in a proinflammatory atherogenic environment, although Tregs plasticity in atherosclerosis has been reported ( 32 , 33 ).…”
Section: Trained Immunity An Innate Immune Memory Is a New Inflammati...mentioning
confidence: 99%